Patient and Caregiver-Derived Health Service Improvements for Better Critical Care Recovery. Issue 12 (7th October 2022) - Haines, Kimberley J.; Leggett, Nina; Hibbert, Elizabeth; Hall, Tarli; Boehm, Leanne M.; Bakhru, Rita N.; Bastin, Anthony J.; Butcher, Brad W.; Eaton, Tammy L.; Harris, Wendy; Hope, Aluko A.; Jackson, James; et al.
Abstract : OBJECTIVES: To engage critical care end-users (survivors and caregivers) to describe their emotions and experiences across their recovery trajectory, and elicit their ideas and solutions for health service improvements to improve the ICU recovery experience. DESIGN: End-user engagement as part of a qualitative design using the Framework Analysis method. SETTING: The Society of Critical Care Medicine's THRIVE international collaborative sites (follow-up clinics and peer support groups). SUBJECTS: Patients and caregivers following critical illness and identified through the collaboratives. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: Eighty-six interviews were conducted. The following themes were identified: 1) Emotions and experiences of patients—"Loss of former self; Experiences of disability and adaptation"; 2) Emotions and experiences of caregivers—"Emotional impacts, adopting new roles, and caregiver burden; Influence of gender roles; Adaptation, adjustment, recalibration"; and 3) Patient and caregiver-generated solutions to improve recovery across the arc of care—"Family-targeted education; Expectation management; Rehabilitation for patients and caregivers; Peer support groups; Reconnecting with ICU post-discharge; Access to community-based supports post-discharge; Psychological support; Education of issues of ICU survivorship for health professionals; Support across recovery trajectory." Themes were mapped to a previously published recovery framework (Timing It Right) that captures patient and caregiver experiences and their support needs across the phases of care from the event/diagnosis to adaptation post-discharge home. CONCLUSIONS: Patients and caregivers reported a range of emotions and experiences across the recovery trajectory from ICU to home. Through end-user engagement strategies many potential solutions were identified that could be implemented by health services and tested to support the delivery of higher-quality care for ICU survivors and their caregivers that extend from tertiary to primary care settings.